2017
DOI: 10.2134/jeq2016.10.0403
|View full text |Cite
|
Sign up to set email alerts
|

Coal‐Bed Methane Water: Effects on Soil Properties and Camelina Productivity

Abstract: Every year, the production of coal-bed natural gas in the Powder River Basin results in the discharge of large amounts of coal-bed methane water (CBMW) in Wyoming; however, no sustainable disposal methods for CBMW are currently available. A greenhouse study was conducted to evaluate the potential to use CBMW as a source of irrigation water for camelina [Camelina sativa (L.) Crantz].We assessed the effects of three CBMW concentrations (0% [1:0], 50% [1:1], and 100% [0:1] tap water to CBMW) on selected soil prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Burkhadt et al [10] in a field study reported that lemongrass and spearmint EO concentrations were significantly affected by CBMW. Sintim et al [26] in a study with three cultivars of the oilseed camelina (Camelina sativa L.) grown in field soil reported that CBMW may have reduced total saturated fatty acids, but it had no effect on mono-and poly-unsaturated fatty acids. Since CBMW contains salts and several elements in elevated concentrations, it is difficult to separate which of these would be responsible for the observed effects on plant secondary (EO) and primary (FA) synthesis and accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Burkhadt et al [10] in a field study reported that lemongrass and spearmint EO concentrations were significantly affected by CBMW. Sintim et al [26] in a study with three cultivars of the oilseed camelina (Camelina sativa L.) grown in field soil reported that CBMW may have reduced total saturated fatty acids, but it had no effect on mono-and poly-unsaturated fatty acids. Since CBMW contains salts and several elements in elevated concentrations, it is difficult to separate which of these would be responsible for the observed effects on plant secondary (EO) and primary (FA) synthesis and accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Techniques aimed at mitigating soil salinity, such as over-irrigation to increase salt leaching (Norvell et al, 2009), PW blending (Atia, 2017;Martel-Valles et al, 2017;Mullins and Hajek, 1998;Sintim et al, 2017), and PW desalination (Sousa et al, 2017;Weber et al, 2017) to reduce salt inputs to the soil, as well as soil and irrigation water amendments to mitigate soil sodicity (Bennett et al, 2016;Johnston et al, 2008), have been tested in field experiments. However, these techniques were used individually, but not in combination to maximise their impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Techniques, such as over-irrigation to increase salt leaching (Norvell et al, 2009), PW blending (Atia, 2017;Martel-Valles et al, 2017;Mullins and Hajek, 1998;Sintim et al, 2017), irrigation with reverse osmosis-treated PW (ROPW) (Sousa et al, 2017;Weber et al, 2017), as well as soil and irrigation water amendments (Ali et al, 2018;Bennett et al, 2016;Ganjegunte et al, 2005;Johnston et al, 2008;Vance et al, 2008) have been used in field experiments to mitigate soil salinisation and sodification caused by irrigation with PW.…”
Section: Introductionmentioning
confidence: 99%